Effectiveness of Aloe Vera and Cabbage Leaf Compress on Breast Swelling Pain in Post-Partners in Bogor Barat District, Bogor City - Darsini Suwarno; Vivi Silawati; Retno Widowati (International Health Sciences Journal, 2024)
ASEAN data in 2022 stated that 76,543 postpartum mothers experienced breast engorgement. 17.2 million postpartum mothers worldwide experience breast pain problems while breastfeeding. In Indonesia, the incidence of breastfeeding mothers experiencing breast engorgement reached the highest figure of 37.2% and 16% of working breastfeeding mothers experienced breast engorgement. Breast engorgement is interpreted as increased venous and lymph flow in the breasts to prepare for lactation. This is due to overdistension of the lactation ducts, causing breast swelling pain, and breast engorgement accompanied by an increase in body temperature. The study used a quasi-experimental design with a pretest-posttest two-group design. The sample consisted of 30 postpartum mothers who experienced breast engorgement pain and were divided into 2 intervention groups, namely aloe vera compresses and cabbage compresses, the intervention was carried out for 14 days. The instrument used was the Visual Analogue Scale (VAS). Data were analyzed using the Paired T-Test and Independent T-Test. In the Independent Sample T-Test, the p-value of the VAS scale for the aloe vera group was 0.019 <0.05 with an average score of 2.0 and the VAS scale for the cabbage group was 0.037 <0.05 with an average score of 1.87.